Water requirements of irrigated crops in the Mujib basin using geospatial techniques - Rasha AbuRukaba (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
The study aims to calculate the water requirements of irrigated crops in a way of accumulation of Evaporationtranspiration we allow crops to estimate the volume of water embodied in every hectare of crops in the Mujib Basin, by employing geospatial techniques in mapping the distribution of water supply sources and the map of irrigated areas and their main crops; has been relied on Satellite data from the Landsat 8 satellite, and daily climate data for the 2016/2017 water year, to calculate daily evaporationtranspiration. The study concluded to reach specialized maps with accurate details that define irrigated areas where the irrigated areas were concentrated in the Mujib basin in two main regions: (south of Amman - Madaba and Giza), around the valleys (Al-Wala - Mujib), the main prevailing irrigated crops were classified into: (olive trees, trees Fruits, field crops, and summer vegetables). The water supply sources in the Mujib basin varied between rain and surface, underground and unconventional sources represented by treated wastewater, and the results of the water demand assessment for irrigated crops in the Mujib basin showed the form of evaporationtranspiration we have been able to the water year 2016/2017 that he needed every hectare of irrigated olive trees Of the water 540 mm³, fruit trees 669 mm³, field crops 865mm³, and vegetables for the summer season 368 mm³. The study recommends the use of geospatial techniques in studying the spatial and temporal changes of crops in the irrigated areas, estimating their water needs per hectare for all water basins in Jordan, encouraging night irrigation especially in the dry months, and cultivating in the wet months to reduce evaporationtranspiration ETo.